2018
DOI: 10.1161/jaha.117.008226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma 8‐OH‐Deoxyguanosine and Cardiovascular Disease and Survival in Type 2 Diabetes Mellitus: Results From the ADVANCE Trial

Abstract: Background8‐Oxo‐2′‐deoxyguanosine (8‐oxo‐2′‐dG) is a biomarker of oxidative DNA damage that is associated with cardiovascular disease and premature mortality in the general population. Although oxidative stress has a proven role in cardiovascular complications in diabetes mellitus, evidence for a relationship between plasma 8‐oxo‐2′‐dG and major cardiovascular outcomes in diabetes mellitus is weak.Methods and ResultsA case‐cohort study was performed in 3766 participants with prevalent diabetes mellitus in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
(39 reference statements)
0
15
0
1
Order By: Relevance
“…AOPP levels were also higher in hypertensive patients and in particular, in those with renal complications [43]. In a prospective study, oxidative DNA damage, measured as 8-hydroxy-2-deoxyguanosine (8-OHdG), predicted micro and macrovascular complications in T2DM patients [44]. Experimental studies also highlighted the pathological role of some of these markers: by binding to their common receptor RAGE, AOPP and AGEs activate inflammatory and apoptotic pathways leading to oxidative stress, inflammation and cell death both on cardiomyocytes and renal cells [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…AOPP levels were also higher in hypertensive patients and in particular, in those with renal complications [43]. In a prospective study, oxidative DNA damage, measured as 8-hydroxy-2-deoxyguanosine (8-OHdG), predicted micro and macrovascular complications in T2DM patients [44]. Experimental studies also highlighted the pathological role of some of these markers: by binding to their common receptor RAGE, AOPP and AGEs activate inflammatory and apoptotic pathways leading to oxidative stress, inflammation and cell death both on cardiomyocytes and renal cells [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 12 studies revealed that supplementation with vitamin E was associated with reduced blood glucose and glycated hemoglobin and administration of vitamins C as well as E were associated with lower MDA levels and higher GPx as well as SOD activity [109]. The ADVANCE Trial revealed that 8-oxo-2'-deoxyguanosine levels were correlated with all-cause and cardiovascular mortality in adults with type 2 diabetes mellitus (T2DM) (n = 3766) [110]. Likewise, an independent prospective cohort study revealed a correlation of RNA oxidation with all-cause and cardiovascular mortality risk in patients with T2DM [111].…”
Section: Clinical Evidence For a Role Of Oxidative Stress In Cardiovamentioning
confidence: 99%
“…Whereas a study emphasized the protection of glucagon-like peptide 1 (GLP-1) agonists against oxidative and apoptotic damage in a diabetic mouse model [89], another study supported the role of metformin in improving neurological functions and OS status via the AMPK/mTOR signaling pathway in acute stroke patients with type 2 diabetes [90]. In heart disease, a clinical trial enrolling 3766 adults with prevalent diabetes mellitus illustrated that increased levels of 8-oxo-2′-deoxyguanosine, a biomarker of oxidative DNA damage, were independently associated with elevated cardiovascular mortality [91]. In depression, recent studies have proposed that one possible mechanism linking diabetes and depression was the increase in lipid peroxidation and decrease in antioxidant activity in the hippocampal and prefrontal cortices, which are the areas of the brain associated with mood [92,93].…”
Section: Diabetesmentioning
confidence: 87%